2022
DOI: 10.1177/20534345221124382
|View full text |Cite
|
Sign up to set email alerts
|

The nurse anesthetist’s perception of the role of case manager in four provinces of Indonesia

Abstract: Introduction Integrated and patient-focused healthcare is urgently needed, and there is an important role for case managers in implementing them. However, the understanding of healthcare providers, especially nurse anesthetists, about the role of case managers is still varied and is often considered only as a complement to hospital accreditation. This study aimed to determine the factors that influence the nurse anesthetist’s perception of the role of the case manager. Methods This cross-sectional study involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Lusiana Devi et al 5 aimed to determine the factors that influence the nurse anaesthetist's perception of the role of the care manager in four provinces in Indonesia by using a cross-sectional study. It was reported that the majority of respondents have a positive perception of care managers, whereas authors conclude that socialisation to increase knowledge about care managers is needed to reduce misperceptions about their role.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lusiana Devi et al 5 aimed to determine the factors that influence the nurse anaesthetist's perception of the role of the care manager in four provinces in Indonesia by using a cross-sectional study. It was reported that the majority of respondents have a positive perception of care managers, whereas authors conclude that socialisation to increase knowledge about care managers is needed to reduce misperceptions about their role.…”
mentioning
confidence: 99%
“…It was reported that the majority of respondents have a positive perception of care managers, whereas authors conclude that socialisation to increase knowledge about care managers is needed to reduce misperceptions about their role. 5…”
mentioning
confidence: 99%